Analysis of the State and Development of the Economy of the Republic of Uzbekistan in the Conditions of Digitalization and Implementation of Strategic Reforms - B. A. Begalov; I. E. Zhukovskaya; A. A. Mamadzhanov (Статистика и экономика)
Purpose of the study. The purpose of this paper is to analyze the development of the economy of the Republic of Uzbekistan in the context of digital transformation, as well as reforms aimed at liberalizing all aspects of public life, democratizing the state and society, as well as identifying the best practices for modernizing industries and areas of the national economy to achieve the highest results of the country’s competitiveness in the world economic market.Materials and methods. The main sources for analysis and preparation for publication of this article were official statistical data from the Statistics Agency under the President of the Republic of Uzbekistan. When writing the article, the authors used methods of statistical analysis of quantitative data, synthesis, methods of systematic generalization of the results of questionnaires and expert surveys, monographic research, methods of working with specialized software products, digital platforms and services, as well as specialized methods of searching and processing data when working with statistical reports and analytical information presented on the corporate portal of the Statistics Agency under the President of the Republic of Uzbekistan.Results. The authors of the article studied the regulatory framework for reforming the national economy of the Republic of Uzbekistan, analyzed the digital mechanisms for implementing the strategy “Digital Uzbekistan - 2030” and, based on a thorough study of the strategic directions of economic development, revealed that the reforms being implemented, high demands and responsibility for fulfilling the set goals tasks to achieve goals are quite effective. In addition, this study showed that the applied digital solutions, such as digital platforms and digital services specially developed for the field of statistics, artificial intelligence technologies, BIGDATA, cloud computing, business analytical engines, as well as specialized software products, the ability to work with mobile devices and the use of satellite navigation to collect statistical data in the regions of the country make it possible to conduct a multidimensional analysis of business processes of economic objects of the national economy and develop optimal management decisions for the further effective development of industries and spheres of the economy of the Republic of Uzbekistan.Conclusion. Research conducted as part of this paper shows that today, within the framework of strategies developed in the Republic of Uzbekistan for the effective development of the country’s economy, good results have been achieved. However, in certain sectors and areas of the national economy, qualitative transformations are still needed, based on the introduction of advanced methodological foundations, innovative technological and management solutions in order to increase the country’s competitiveness. It is necessary to further improve the technical and technological base of industrial and agricultural enterprises, ensure the high-quality development of human capital, improve the methods and forms of functioning of business structures in the digital economy, identify new development drivers for balanced economic growth and improving the quality of life of the country’s population.